Pengawasan Sekolah Unggul Berbasis Soft Skills: Studi Kasus di SMAN 1 Sidoarjo - Karyanto Karyanto; Endang Sulistiyorini; Warsiman Warsiman (Universitas Pendidikan Mandalika, 2022)
The research aims to identify the pattern of supervision used by SMAN 1 Sidoarjo in implementing the excellent school program based on soft skills. This study uses a qualitative descriptive approach. Principals, teachers, students, staff and everyone else involved in SMAN 1 Sidoarjo's excellent school program focused on soft skills were the study's subjects. The research's primary data collection methods are interviews, observation, and documentation. The results showed that SMAN 1 Sidoarjo's excellent school supervision program based on soft skills involved internal elements such as the school itself, the administrator as the primary element who manages the academic community, and teachers who supervise students. The purpose of internal supervision is to ensure that the soft skills program is implemented effectively and efficiently. The education department, supervisors, school committees, parents/guardians, and the community all participate in external supervision. External supervision is necessary for the program's development and maintenance. The result shows that supervision in the implementation of a program is essential to do to maintain the sustainability of the program.